An empirical evaluation of macroeconomic surveillance in the European Union - Jens Boysen-Hogrefe; Nils Jannsen; Martin Plödt; Tim Schwarzmüller (Kiel Institute for the World Economy (IfW), 2015)
The EU's macroeconomic surveillance mechanism, namely the Macroeconomic Imbalance Procedure (MIP), is based on the so-called Scoreboard, which comprises a set of indicators that serve as a signalling device for potentially harmful macroeconomic developments. We first evaluate the early warning properties of the Scoreboard indicators with regard to financial crises. We then analyze the role of emerging crisis signals from the Scoreboard for the subsequent steps of the MIP (In-Depth Reviews), in which the gravity of imbalances and policy recommendations are specified. The results of our study help to identify ways to improve the current set-up and ultimately to deliver more transparent and effective policy advice.
Keywords: E02; E61; C25; 330; Macroeconomic Imbalance Procedure; early warning indicators; signals approach; financial crises